Misconceptions in primary science - Allen, Michael (Maidenhead : Open University Press, 2010)
'This essential book offers friendly support and practical advice for dealing with the common misconceptions encountered in the primary science classroom.''Most pupils will arrive at the science lesson with previously formed ideas, based on prior reasoning or experience. However, these ideas are often founded on common misconceptions, which if left unexplained can continue into adulthood. This book offers advice for teachers on how to recognise and correct such misconceptions.''Michael Allen describes over 100 common misconceptions and their potential origins, and then explains the correct principles. He suggests creative activities to help students to grasp the underlying scientific concepts and bring them alive in the classroom.''This easy to navigate guide is grouped into three parts: life processes and living things; materials and their properties; and physical processes.'
Includes bibliographical references (p. [217]-227) and index
Keywords: Science -- Study and teaching (Elementary) -- United Kingdom; Common fallacies; Errors, Scientific